Effect of microcrystalline cellulose on the strength of oil palm empty fruit bunch paper - Ismail, Faris Syahiran; Mohamed @ Asa'ari, Ainun Zuriyati; Jawaid, Mohammad (IOP Publishing, 2018)
Oil palm empty fruit bunch (EFB) is one of the most copious residues which are left behind after the oil refining process. It is categorized as short fiber which can be used in the production of pulp and paper. In most cases, EFB fibers need other supporting agent to enhance their wet and dry strength of paper properties. Therefore, the aim of this study is to investigate the effect of paper strength after incorporating different percentage of microcrystalline cellulose (MCC) of 0, 3, 6 and 9% with EFB fibers. The standard method in producing the hand-sheet was applied. Comparison is carried among all samples to determine the optimum percentage of MCC which is suitable to strengthen the paper. Results showed that physical properties of paper in terms of porosity do not have significant effect while the opacity was slightly decreased. The mechanical properties such as tensile strength and tear resistance for MCC papers are better especially paper tensile strength. The scanning electron microscopy (SEM) image showed the morphological structure of paper surface that contains without and with MCC. In conclusion mechanical properties of the hand-sheets are improved with the incorporation of less than 10% MCC into the pulp fibers.